Preliminary Studies on the Biology and Ecology of Chlamydarus pullus (Reuter) (Heteroptera: Miridae) in Greenland. - Böcher, Jens (Meddelelser om Grønland, 1971)
Only one species of Chlamydatus CURT., C. pullus (REUT.), is found in Greenland, where it occurs in a parthenogenetic form. The known distribution in Greenland indicates that the species is absent only in the northernmost parts. The habitat of C. pullus is described in detail here, and microclimatic measurements from the habitat are presented. The results of preliminary experiments on the species’ relationship to humidity and temperature indicate a preference for the dry and hot conditions found in the habitat. In Greenland C. pullus has only one annual generation and overwinters in the egg-stage. The species is phytophagous and polyphagous, occasionally being a predator on small insects. Important food-plants appear to be Polygonum viviparum and Potentilla spp.